Gênero, ciência e contexto regional : analisando diferenças entre docentes da pós-graduação de duas universidades brasileiras - BORGES, Elinielle Pinto (Instituto Federal do Amapá, 2021)
This study aims to examine gender inequality in academic tasks of graduate faculty, as well as identify mechanisms that contribute to the establishment and perpetuation of these inequalities. The theoretical discussion presents arguments about gender differences in society in general, and science in particular. The empirical approach selected as a field of study two federal universities: UFRJ and UFMA, aiming also to identify regional differences, through quantitative and qualitative analysis. For the quantitative approach we used secondary data already worked on during the study Leta et al. (2013). A subset of this data on the two institutions was generated for this study which involved information about a total of 2667 teachers-researchers. The qualitative approach involved interviews conducted with 14 graduate coordinators of the universities mentioned. The interview script aimed to detect differences in gender culture in career choices, in the exercise of academic tasks, in the establishment of obstacles in a scientific career, and in the overload of activities related to education of children. The analysis of the quantitative data showed, among other things, that the UFRJ courses have outperformed those of UFMA. Focusing on gender inequalities, there was a better balance between men and women in the performance of academic tasks in UFMA than at UFRJ. The analysis of the interviews showed that teachers-researchers, men and women, tend not to see gender differences in academia and that both sexes carry prejudices about the differences in skills between men and women. The statements of the respondents also suggest that the weight of the gender imbalance in the performance of household chores, and their impact on the activities of women is felt even in the sense of guilt carried by women who reached the top of the scientific career. Regarding regional differences, the researchers of UFMA are shown to feel barriers and difficulties in the exercise of scientific activity in a less developed region.